JENIS-JENIS Hoya (APOCYNACEAE) DI GUNUNG SIDOLE, KECAMATAN AMPIBABO, KABUPATEN PARIGI MOUTONG, SULAWESI TENGAH - Roland P P Ahmad; Ramadanil (Biology Department, Mathematics and natural science, Tadulako University, 2020)
A research about species diversity of Hoya (Apocynaceae) in Sidole Mountain, Ampibabo District, Parigi Moutong Regency of Central Sulawesi has been conducted from December 2018 to March 2019. The research was conducted by using botanical exploration method that aim to record and describe species of Hoya based on morphological characters The results showed that there were 2 species of Hoya namely H. camphorifolia Warb and H. imbricata Decne.